Research Dynamics in Islamic Religious Education Curriculum: Insights from a Bibliometric Study - Siti Muthiatul Hasanah; Heru Wibowo (Intiqad: Jurnal Agama dan Pendidikan Islam, 2026)
The urgency of this research lies in the urgent need to understand the dynamics of the Islamic Religious Education (PAI) curriculum in the context of 21st century education transformation that emphasizes religious moderation, digital literacy, and inclusivity. Given the lack of studies that specifically map the development of the PAI curriculum bibliometrically, this study aims to provide a comprehensive mapping of trends, collaborations, authors, and themes that developed from 2015 to 2025. The method used is Scopus data-based bibliometric analysis with the PRISMA approach and processing using R software (Bibliometrix). The results show that publications will increase significantly in 2024, dominated by the social sciences and humanities, with Indonesia as the main contributor to global research. The thematic findings show that topics such as "curriculum", "religion", and "human" are the main driving themes, while concepts such as "inclusive education" and "Islamic moderation" have the potential to develop in the future. The novelty of this study lies in its explicit focus on the PAI curriculum, as well as a detailed mapping of international collaboration and thematic directions. Its contribution is significant to the development of Islamic education policies that are more contextual, progressive, and relevant to global agendas such as the SDGs.